2016
DOI: 10.1007/s13361-015-1331-7
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis of Proteins in Highly Concentrated Solutions by Dialysis-Coupled Hydrogen/Deuterium Exchange Mass Spectrometry

Abstract: Abstract. When highly concentrated, an antibody solution can exhibit unusual behaviors, which can lead to unwanted properties, such as increased levels of protein aggregation and unusually high viscosity. Molecular modeling, along with many indirect biophysical measurements, has suggested that the cause for these phenomena can be due to short range electrostatic and/or hydrophobic protein-protein interactions. Hydrogen/deuterium exchange mass spectrometry (HDX-MS) is a useful tool for investigating protein con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 33 publications
0
22
1
Order By: Relevance
“…33 Mass spectrometry coupled to HX (HX-MS), extends the HX technique to complex, multi-domain macromolecules like mAbs. [37][38][39][40][41][42][43] Recently, we described a novel HX-MS method to map protein interfaces formed between mAbs undergoing reversible protein-protein interactions directly at up to 60 g/L. 39 Here, we applied this technique to investigate the molecular mechanism by which an IgG1 mAb (mAb-J) undergoes reversible self-association, and further probed this mechanism by a variety of other biophysical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…33 Mass spectrometry coupled to HX (HX-MS), extends the HX technique to complex, multi-domain macromolecules like mAbs. [37][38][39][40][41][42][43] Recently, we described a novel HX-MS method to map protein interfaces formed between mAbs undergoing reversible protein-protein interactions directly at up to 60 g/L. 39 Here, we applied this technique to investigate the molecular mechanism by which an IgG1 mAb (mAb-J) undergoes reversible self-association, and further probed this mechanism by a variety of other biophysical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36] Hydrogen exchange-mass spectrometry (HX-MS) is a wellestablished high-resolution technique for exploring protein dynamics and conformational flexibility including the effect of excipients on aggregation propensity and RSA in low and high concentration mAb formulations. 13,[32][33][34][35][36][37][38] Under certain circumstances, such as RSA or interaction with excipients, the exchange rate can be altered in specific regions, indicating local alterations of backbone dynamics. 13 HX-MS has been used to elucidate molecular effects of excipients [32][33][34][35][36][37][38][39] and chemical changes (e.g., asparagine deamidation, 40 deglycosylation, 35 posttranslational modifications, 41 and engineered point mutations 42 ) on mAb conformational dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…13,[32][33][34][35][36][37][38] Under certain circumstances, such as RSA or interaction with excipients, the exchange rate can be altered in specific regions, indicating local alterations of backbone dynamics. 13 HX-MS has been used to elucidate molecular effects of excipients [32][33][34][35][36][37][38][39] and chemical changes (e.g., asparagine deamidation, 40 deglycosylation, 35 posttranslational modifications, 41 and engineered point mutations 42 ) on mAb conformational dynamics. We recently demonstrated that a particular IgG1 (mAb-J) undergoes extensive RSA at high protein concentrations via electrostatic attractive interactions between segments of the Fab and Fc domains as determined by HX-MS analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, HDX-MS workflows designed for the analysis of high concentration protein samples have been described. 20,21 For example, a recently described HDX-MS methodology that relies upon reconstituting lyophilized mAb powders in a deuterated buffer was able to characterize mAb structures at 60 mg/mL. 20 This approach identified protein-protein interfaces associated with a concentration-dependent reversible selfassociation.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, a dialysis-coupled HDX-MS strategy was recently reported for mAb analysis, in which passive dialysis microcassettes are used for HDX labeling. 21 While this approach successfully sampled high concentration (200 mg/ mL) IgG4 formulations for comparison with low concentration (3 mg/mL) samples, the long timescales needed for dialysis likely render many known modes of protein motion inaccessible to the technology.…”
Section: Introductionmentioning
confidence: 99%